Mechanism of action of sprG1-encoded type I toxins in Staphylococcus aureus: from membrane alterations to mesosome-like structures formation and bacterial lysis - Fermon, Laurence; Burel, Agnès; Ostyn, Emeline; Dréano, Stéphane; Bondon, Arnaud; Chevance, Soizic; Pinel-Marie, Marie-Laure (Frontiers in Microbiology, 2023)
sprG1/SprF1 is a type I toxin-antitoxin system located on Staphylococcus aureus prophage. It has previously been shown that the two toxins, SprG131 and SprG144, encoded by the sprG1 gene, are two membrane-associated peptides structured in a single α-helix. Overexpression of these two peptides leads to growth inhibition and even S. aureus death. In this study, we investigated the involvement of each peptide in this toxicity, the sequence requirements necessary for SprG131 toxicity, and the mechanism of action of these two peptides. Our findings show that both peptides, when expressed individually, are able to stop growth, with higher toxicity observed for SprG131. The combination of a hydrophobic domain and a charged domain located only at the C-terminus is necessary for this toxicity, likely to retain the orientation of the transmembrane domain. A net cationic charge for SprG131 is not essential to induce a growth defect in S. aureus. Furthermore, we established a chronology of toxic events following overexpression to gain insights into the mode of action of SprG144 and SprG131. We demonstrated that mesosome-like structures are already formed when membrane is depolarized, about 20 minutes after peptides induction. This membrane depolarization occurs concomitantly with a depletion of intracellular ATP, leading to S. aureus growth arrest. Moreover, we hypothesized that SprG144 and SprG131 do not form large pores in the S. aureus membrane, as ATP is not excreted into the extracellular medium, and membrane permeabilization is delayed relative to membrane depolarization. The next challenge is to identify the conditions under which SprG144 and SprG131 are naturally expressed, and to uncover their potential roles during staphylococcal growth, colonization, and infection.